2015
DOI: 10.5376/jmr.2015.05.0010
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Potentiality of Root Extracts of <i>Annona reticulata</i> Linn. Against the Filarial Vector <i>Culex quinquefasciatus</i> Say (Diptera: Culicidae)

Abstract: Present study was undertaken to evaluate the mosquito larvicidal potentiality of root extracts of Annona reticulata Linn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Numerous studies have revealed a variety of herbs with larvicidal, pupicidal, adulticidal, phagodeterrence, oviposition deterrence, repellent, and smoke toxic effects against mosquitoes [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed a variety of herbs with larvicidal, pupicidal, adulticidal, phagodeterrence, oviposition deterrence, repellent, and smoke toxic effects against mosquitoes [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to synthetic mosquitocides, attempts are now being made to control the mosquito population using plant-derived compounds and phytochemicals that have effective mosquitocidal characteristics. Secondary metabolites in these natural products have larvicidal [ 7 ], pupicidal [ 8 ], adulticidal [ 9 ], repellent [ 10 ] and oviposition deterrence [ 11 ] effects on mosquitoes. These plant-based remedies are biodegradable, environment friendly, less damaging to non-target species, and relatively inexpensive [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present need is to investigate a novel mosquitocide that would be biodegradable, target specific and non-detrimental to any other life forms [8] though some biocontrol agents are reported to reduce mosquito population [9][10][11] . Usually, some of the plant derived molecules are known to have such qualities that proclaim them to be most suitable to formulate mosquito larvicide [12,13] , pupicide [14] , adulticide [15] and repellents [16] along with other attributes like antibacterials [17] , anthelmintics [18,19] etc. Originating from South and Southeast Asia, Michelia champaca L. is a tall, evergreen tree that is mostly cultivated for its lumber.…”
Section: Introductionmentioning
confidence: 99%